2002
DOI: 10.1080/0891693021000056703
|View full text |Cite
|
Sign up to set email alerts
|

Association of Single Nucleotide Polymorphisms of the Interleukin-10 Promoter Gene and Susceptibility to Primary Biliary Cirrhosis: Immunogenetic Differences in Italian and Japanese Patients

Abstract: Several lines of data suggest that genetic factors play an important role in the onset and/or progression of primary biliary cirrhosis (PBC). Since PBC is an autoimmune disease, it is reasoned to assume that genes encoding cytokines may confer susceptibility to disease. Amongst these factors, interleukin-10 (IL-10) has received significant attention. The promoter region of IL-10 gene has three single nucleotide polymorphisms (SNPs) at positions -1082, -819 and -592. To elucidate the association of the three SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…63 Further, based on experimental evidence of cytokine profiles and its involvement in the development of T helper 1 (Th1) cell responses, SNPs of the promoter region of the IL-10 gene were also analyzed in patients with PBC and controls. 55,63,64 Data from Italian and Japanese series demonstrated that both groups presented a higher prevalence of the À1082G/G genotype. 64 Such association was not confirmed in 77 Chinese patients with PBC.…”
Section: Mhc and Pbcmentioning
confidence: 99%
See 1 more Smart Citation
“…63 Further, based on experimental evidence of cytokine profiles and its involvement in the development of T helper 1 (Th1) cell responses, SNPs of the promoter region of the IL-10 gene were also analyzed in patients with PBC and controls. 55,63,64 Data from Italian and Japanese series demonstrated that both groups presented a higher prevalence of the À1082G/G genotype. 64 Such association was not confirmed in 77 Chinese patients with PBC.…”
Section: Mhc and Pbcmentioning
confidence: 99%
“…55,63,64 Data from Italian and Japanese series demonstrated that both groups presented a higher prevalence of the À1082G/G genotype. 64 Such association was not confirmed in 77 Chinese patients with PBC. 62,63 SNPs of the 1,25-dihydroxyvitamin D receptor (VDR) gene have been investigated in several studies, based on the dual role of vitamin D in the regulation of bone metabolism and inflammation.…”
Section: Mhc and Pbcmentioning
confidence: 99%
“…A number of non-HLA candidate gene studies in PBC interrogated genes known or suspected to be involved with autoimmunity including TNF, CTLA4, PTPN22, PDCD1, IL1, IL2, IL10 , toll like receptors and the vitamin D receptor 2634 . Many of these studies were limited by inadequate power and poor gene coverage (often just a single SNP) and there was little correlation between studies.…”
Section: Pre-gwas: Focus On Immunology and Candidate Genesmentioning
confidence: 99%
“…The latter group, however, more recently described an association of PBC with the IL1-RN intron genotype, comparing frequencies in 77 patients with PBC and 160 controls [62]. Further, based on experimental evidence of cytokine profiles and their involvement in the development of T helper 1 cell responses, SNPs of the promoter region of the IL-10 gene were also analyzed in patients with PBC and controls [53,62,63]. Data from Italian and Japanese series demonstrated that both groups presented a higher prevalence of the -1082G/G genotype [63].…”
Section: Non-mhc Genes In Pbcmentioning
confidence: 99%
“…Further, based on experimental evidence of cytokine profiles and their involvement in the development of T helper 1 cell responses, SNPs of the promoter region of the IL-10 gene were also analyzed in patients with PBC and controls [53,62,63]. Data from Italian and Japanese series demonstrated that both groups presented a higher prevalence of the -1082G/G genotype [63]. Such association was not confirmed in 77 Chinese patients with PBC [61,62].…”
Section: Non-mhc Genes In Pbcmentioning
confidence: 99%